The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/bg-14-617-2017
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale variability in geomorphological settings influences mangrove-derived organic matter export in a tropical bay

Abstract: Abstract. Organic matter (OM) exchanges between adjacent habitats affect the dynamics and functioning of coastal systems, as well as the role of the different primary producers as energy and nutrient sources in food webs. Elemental (C, N, C : N) and isotope (δ 13 C) signatures and fatty acid (FA) profiles were used to assess the influence of geomorphological setting in two climatic seasons on the export and fate of mangrove OM across a tidally influenced tropical area, Gazi Bay (Kenya). The main results indica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
3
15
0
1
Order By: Relevance
“…6A). The association of lagoons and tidal systems with riverine inputs can lead to a dominant contribution of allochthonous carbon to these systems (Signa et al, 2017;Watanabe & Kuwae, 2015), which may partly explain the higher OC stocks found in these environments (Fig 2B), and is coherent with the trend of more positive Δ 13 C values (more dominated by allochthonous C) found, particularly, in lagoons (Fig. 4B).…”
Section: Accepted Articlesupporting
confidence: 58%
“…6A). The association of lagoons and tidal systems with riverine inputs can lead to a dominant contribution of allochthonous carbon to these systems (Signa et al, 2017;Watanabe & Kuwae, 2015), which may partly explain the higher OC stocks found in these environments (Fig 2B), and is coherent with the trend of more positive Δ 13 C values (more dominated by allochthonous C) found, particularly, in lagoons (Fig. 4B).…”
Section: Accepted Articlesupporting
confidence: 58%
“…Two seasonal rivers -Kidogoweni to the northwest and Mkurumudji to the southwest of the bay drains into the Bay. This is in addition to seepage points (Signa et al 2017) that provide the Bay with freshwater input. According to Koppen climate classi cation, the climate of Gazi Bay may be classi ed as tropical wet/dry that is ideal for supporting mangrove growth.…”
Section: Methodsmentioning
confidence: 99%
“…This management block is located 3-5 km from Makongeni village (Fig. 1) and has no direct freshwater in uence (Signa et al 2017). The eastern block is largely managed by Kenya Forest Service (KFS), a state forest agency in charge of forests in Kenya, and there is minimal community involvement.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of principal OM pathways of the food web was carried out using a qualitative approach. Differences in δ 13 C values have been shown to provide information on the contribution of sympagic vs. benthic and pelagic sources to the diet of Antarctic consumers (Calizza et al, 2018;Norkko et al, 2007), reliably reflecting differences in OM pathways between organisms (Careddu et al, 2015;Rossi et al, 2015;Signa et al, 2017b). Similarly, δ 15 N values are known to increase unequivocally across trophic levels, and therefore, provide a robust base to identify trophic position of consumers within food webs (Mancinelli et al, 2013;Post, 2002) The effect of the horizontal and vertical food web structure (i.e.…”
Section: Data Elaboration and Statisticsmentioning
confidence: 99%